Molecular Adsorbent Recirculating System Technique for Liver Failure due to Cardiogenic Shock - Zittermann, Armin; Engel, Markus; Hohnemann, Sigrid; Kizner, Lukasz; Gummert, Jan F. (The Thoracic and Cardiovascular Surgeon, 2013)
Background Systematic data on clinical outcome in patients with liver failure due to cardiogenic shock are scarce.Methods We performed a monocentric retrospective data analysis in 197 cardiogenic shock patients with serum bilirubin levels above 102 µmol/L receiving molecular adsorbent recirculating system (MARS). We assessed clinical outcome, recorded laboratory parameters, and tried to assess risk factors for survival.Results The median duration of MARS was 87 hours (range, 20–315 hours) during a median time period of 9 days (range, 3–736 days). During MARS, 48 to 75% of patients developed infections and gastrointestinal, respiratory, and neurological complications, respectively. Inhospital mortality was 66% (n = 129). Baseline bilirubin levels were comparable between survivors and non-survivors. During MARS, bilirubin values decreased significantly in survivors but not in non-survivors. Of various clinical and biochemical parameters assessed at baseline, the sepsis-related Organ Failure Assessment score remained the only independent predictor of inhospital mortality.Conclusion Inhospital mortality is still unsatisfyingly high in cardiogenic shock patients with liver failure. Future studies should clarify whether MARS can definitively improve survival in these patients.
Keywords: molecular adsorbent recirculating system; cardiogenic shock; inhospital mortality; bilirubin